BE_VERWALTUNGSGERICHT 100 2021 200 vom 5. August 2022 - BE Verwaltungsgericht (2022)
Studiumsausschluss (Entscheid der Rekurskommission der Universität Bern vom 28. Mai 2021; B 14/20) | Prüfungen/Promotionen